Precision Agriculture Ecosystem Innovation through IoT Technology: A Study of Learning Factory Development for Farmer Empowerment in Ngajum Village - Dwi Wulandari; Otto Fajarianto; Putra Hilmi Prayitno; Fuad Indra Kusuma; Ari Gunawan; Afis Baghiz Syafruddin; Andi Basuki (CV RIFAINSTITUT, 2025)
Precision agriculture is an innovative approach that integrates digital technology to improve the efficiency and productivity of the agricultural sector. This study aims to develop a precision agriculture ecosystem through the implementation of a Smart Agriculture Greenhouse based on the Internet of Things (IoT) as a learning factory model for fostering farmer independence in Ngajum Village. The methods used include a qualitative-descriptive approach with field studies, observations, and in-depth interviews with farmers, assistants, and local stakeholders. The results of the development show that the use of IoT technology in smart greenhouses allows real-time monitoring and control of the agricultural environment, thereby increasing the accuracy of decision-making in cultivation. In addition, the learning factory concept can be a contextual learning medium for farmers to master modern agricultural skills practically. This program also encourages the transformation of farmers' mindsets from conventional practices to data-based and technology-based practices. The ecosystem that is formed acts as a center for education, production, and sustainable agricultural innovation at the village level. These findings show that collaboration between technology, education, and community empowerment can create an adaptive and replicable smart agriculture model to support local food independence. The development of an ecosystem like this has the potential to be a reference in agricultural transformation in other rural areas